Does gestational diabetes result in cochlear damage?. Issue 11 (17th November 2014) - Selcuk, A; Terzi, H; Turkay, U; Kale, A; Genc, S
Abstract: Background: Glucose metabolism has a significant impact on inner-ear physiology. Therefore, hearing may be affected in gestational diabetes. Method: A matched case–control study was performed to evaluate 27 patients with gestational diabetes and 31 non-diabetic pregnant women with similar demographic characteristics. A medical history was taken for each participant, and otological inspections and high-frequency audiometry tests were performed. Results: There were no significant differences in average pure tone air–bone hearing thresholds between the groups ( p  > 0.05). However, evaluation of high-frequency hearing thresholds indicated significantly increased auditory thresholds at 10 kHz and 12 kHz for right ears and at 8, 10, 12 and 14 kHz for left ears in the gestational diabetes group ( p  < 0.001). Conclusion: An investigation into cochlear damage in gestational diabetic patients showed significant high-frequency hearing loss. Further studies are needed to validate these findings in different ethnic groups and geographical populations.